Transformational leaders in the Canadian Counselling and Psychotherapy Association: An Interview With William A. Borgen - Baucom, Daniel J.; Gray, Neal D. (Canadian Journal of Counselling and Psychotherapy, 2023)
This article, the third in a concurrent series highlighting leaders who have been instrumental in shaping the profession in Canada, is an interview with William A. Borgen, a prominent leader in the Canadian counselling profession. This article focuses on Bill’s achievements during his career and his recommendations for the future of the profession in Canada. In particular, the interview provides insight, guidance, and wisdom for influencing future leaders in counselling.